2021
DOI: 10.3917/spub.211.0077
|View full text |Cite
|
Sign up to set email alerts
|

Intégration de la santé mentale dans les services de soins de santé primaires en République démocratique du Congo

Abstract: réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit de l'éditeur, en dehors des cas prévus par la législation en vigueur en Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…It should follow the correct strategy of providers and nonproviders of care, (ii) ensure that primary mental health care also includes brief psychotherapeutic interventions, (iii) promote recovery-oriented community interventions for people with chronic disabling mental disorders, (iv) conceptualize training as a continuous process of strengthening clinical skills through supervision, (v) involve community partners in psychosocial interventions, (vi) integrate changes toward primary mental health care into broader health policy reforms, and (vii) promote intersectoral approaches to address the social determinants of mental health. Most of these recommendations are feasible in the Congolese context since they have been successfully tested in the health district of Lubero in the eastern region of the DRC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should follow the correct strategy of providers and nonproviders of care, (ii) ensure that primary mental health care also includes brief psychotherapeutic interventions, (iii) promote recovery-oriented community interventions for people with chronic disabling mental disorders, (iv) conceptualize training as a continuous process of strengthening clinical skills through supervision, (v) involve community partners in psychosocial interventions, (vi) integrate changes toward primary mental health care into broader health policy reforms, and (vii) promote intersectoral approaches to address the social determinants of mental health. Most of these recommendations are feasible in the Congolese context since they have been successfully tested in the health district of Lubero in the eastern region of the DRC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the country has only 6 public psychiatric hospitals and a dozen private mental health centers with 500 beds for nearly 90 million inhabitants, almost all of which are in located cities [ 23 ]. The coverage of mental health services remains very low (less than 5%); however, mental health provision is severely lacking in primary care services nationwide [ 24 ], and only 3% of PHC services have been able to integrate mental health care supply into their activity packages [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study in Tshopo Province in the DRC indicated that community health workers provide health care, including mental health care, suggesting that task-shifting would work in their favor [31]. The rst experience with mental health integration in the North Kivu province in the DRC showed that community health workers contributed signi cantly to mental health promotion through awareness-raising, community mobilization, follow-up of patients during home visits, and more [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the DRC, given that the coverage of mental health services is estimated at a dismal 5% [13], traditional medicine remains the main source of care for the population in both urban and rural areas [14].…”
Section: Introductionmentioning
confidence: 99%